Assessment on the Integration of the Basic Education Department of Notre Dame of Marbel University: Input for Strategic Management Plan - Wilter Friales; Allan Sumadic; Leann Jester Rosali (Philippine Association of Institutions for Research, Inc., 2022)
The term integration refers to merging the Elementary and High School Departments. The merging entailed alignment of the curriculum and management system from kindergarten to the secondary levels, where there is a unified set of administrative teams for both elementary and high school to plan, implement, monitor, and evaluate the curriculum and other administrative components. Using a descriptive research design, this study assessed the implementation of the integrated system of basic education at Notre Dame of Marbel University. Specifically, this study has determined the level of satisfaction of the personnel and retirees on the implementation of the integrated system of the basic education department of Notre Dame of Marbel University; and determining the strengths and weaknesses of the implementation of the integrated system as perceived by the personnel and retirees of NDMU-IBED. The result of the study reveals that all the areas being assessed, such as the Organizational Structure, Academic/Instructional Management, Program Implementation Scheme, Human Relationship, Leadership, and Participation, have obtained very satisfactory results. Strengths and Weaknesses were also identified in each of the areas mentioned. It can be concluded that the integrated system being implemented in the basic education of Notre Dame of Marbel University has brought more positive changes in terms of the organizational structure, academic management, program implementation monitoring scheme, human resource relationship, leadership, and participation.